THE ROLE OF TEACHERS IN SHAPING STUDENTS' CHARACTER AND COMPETENCE TOWARDS A PROGRESSIVE INDONESIA - Silalahi, Verry Albert Jekson Mardame (jfpublisher, 2025)
Education serves as the cornerstone in shaping the next generation of quality citizens, with teachers playing a pivotal role not only in knowledge transfer but also in cultivating students’ character, competence, and moral integrity. This descriptive qualitative study explores the transformative impact of educators as role models and moral guides in fostering noble values and competencies essential for addressing complex global challenges. Through an in-depth examination of innovative and adaptive learning strategies, the research highlights how teachers create conducive, student-centered learning environments that support the vision of a sustainable and developed Indonesia. Findings reveal that effective pedagogical practices—rooted in empathy, innovation, and ethical commitment—strengthen the alignment between education and national development goals. The study emphasizes that teacher professionalism, continuous training, and institutional support are critical in producing high-integrity human resources capable of driving national progress. Furthermore, integrating character education into curriculum development ensures that students are not only academically proficient but also ethically grounded. Ultimately, this article argues for a paradigm shift in education policy that recognizes teachers as central architects of national resilience and sustainable development. Strengthening their role is not merely an educational imperative but a strategic necessity for Indonesia’s future.